Pengaruh Kepemimpinan Kepala Madrasah Terhadap Kinerja Guru - Elistatia, Usi (Proceedings Series of Educational Studies, 2024)
Abstract Education plays a vital role in preparing high-quality human resources (HR) to build a nation and a country. Teachers hold a central role in the educational process, as they interact directly with students in daily learning activities at school. The success of education in madrasahs largely depends on the ability of the madrasah principal to lead and manage available resources. This study aims to analyze the influence of madrasah principal leadership on teacher performance at MTs YAPSI Sumber Jaya, West Lampung Regency. The background of the study shows that although the principal has performed well and met competency standards, there are still weaknesses in influencing teacher discipline, such as tardiness and leaving earlier than scheduled. This research uses a quantitative approach with a survey method, where data is collected through questionnaires from the entire population of teachers at the madrasah, totaling 20 individuals. Statistical analysis was conducted to test the hypothesis regarding the impact of madrasah principal leadership on teacher performance. The results show that the leadership of the madrasah principal significantly affects teacher performance, with a t-value of 3.212 and a t-table value of 2.086, meaning Ha is accepted and H0 is rejected. The coefficient of determination (R²) of 0.364 indicates that 36.4% of teacher performance is influenced by the leadership of the madrasah principal, while the remaining 63.6% is affected by other factors. Based on these findings, it can be concluded that the madrasah principal's leadership plays an important role in improving teacher performance, although other factors also contribute to overall teacher performance.